RISK CONTROL IN THE SMOKED TILAPIA PRODUCTION PROCESS USING THE HIRARC AND FTA METHODS - Mia Nur Faidah; Inggit Marodiyah (Antis Publisher, 2025)
Objective: The aim of this research is to determine what factors cause work accidents and determine appropriate and effective risk control strategies. Method: The methods used to carry out the analysis are the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) and FTA (Faut Tree Analysis) methods. Results: The results of this research are able to reduce the risk of danger arising from work accidents by requiring workers to wear gloves and boots during the production process. Novelty: In the process of producing smoked tilapia there is a risk of dangers that have the potential to cause work accidents. The dangers that often occur are cuts on the hands, injuries to the hands during production activities and exposure to sparks due to lack of caution. Therefore, it is necessary to make efforts to prevent work accidents and work-related diseases, one of which can be done by means of risk analysis.